Shari'a in Everyday Life in Sydney: An Analysis of Professionals and Leaders Dealing with Islamic Law - Possamai, Adam (Journal for the academic study of religion, 2017)
This article explores how Shari'a is conceptualised and experienced by 27 Muslim legal professionals and leaders in Sydney. It analyses qualitative data on issues with regards to the experience of Muslims with Shari'a, on how it can be improved in Australia and on how compatible is Shari'a with the Australian legal system. It also discusses Shari'a tribunals and financial opportunity. While we do not find any convincing arguments for the push to the further implementation of Shari'a in Australia, we find that despite political objections Shari'a is a vital part of everyday life for observant Australian Muslims. We are arguing that the popular political debate around Shari'a is in critical need of more exposure to balanced Muslim voices that can be heard above the popular political resistance to any manifestation of Shari'a.